Self-Efficacy of English Language Teachers With Low and High Curriculum Literacy in Indonesian Schools - Burhanuddin Yasin; Usman Kasim; Faisal Mustafa; Saiful Marhaban; Endang Komariah (Universidad Nacional de Colombia, 2022)
This study explores the difference in self-efficacy between high school English language teachers with two levels of curriculum literacy. The data were collected using a curriculum literacy test and a self-efficacy scale that were delivered online to 251 English teachers in Indonesia. The respondents were split into two groups based on their curriculum literacy scores. The findings show that teachers with higher curriculum literacy levels were more self-efficacious than those with a lower level of curriculum literacy. This implies that curriculum related courses in preservice teacher programs need to be improved, and in-service teacher training should focus on curriculum knowledge.